CODE SWITCHING USED IN EFL CLASSROOM AND IN RESEARCH PROPOSAL SEMINAR INTERACTION OF EFL STUDENTS - Maria Ramasari; Febria Kumalasari (Universitas Negeri Padang, 2018)
The aim of this research was to describe the code switching used in EFL classroom and in research proposal seminar interaction of EFL students. Qualitative research with descriptive method was used in conducting this research. Based on the result of data analysis, there was 1 type of code switching used: Inter-Sentential Code Switching. Whereas, there was 2 forms found in EFL classroom: 1. English – Bahasa switching, 2. Bahasa – English Switching. Moreover, there were 4 forms found in research proposal seminar interaction of EFL students: 1. English – Bahasa Switching, 2. Bahasa – English Switching, 3. English – Palembang-Lubuklinggau Switching, 4. Palembang – Lubuklinggau – English Switching. The use of code switching was caused by some reasons. They were: 1) Lack of vocabulary of English, 2) Habitually, and 3) Participants and setting. The dominant reason was situational code switching; a change in the situation that causes the bilingual switches from one code to others. It could be the setting, participants (subject) and norm of interaction. The researcher suggests to EFL speakers that they should increase and intensify their English vocabulary mastery, create a positive habitual in practicing English to others in their environment, especially in formal setting. In her point of view, code switching could be used and give useful for certain situation to keep the interaction run smoothly and avoid misunderstanding each others.